THE PROPERNESS OF MUTATION TEXTBOOK USING METACOGNITIVE AND MIND MAP STRATEGY FOR SENIOR HIGH SCHOOL GRADE XII - Lestari, Rita Puspa; Susantini, Endang (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
map technique to facilitate learners to understand the concept. This research aimed to produce a valid and practical mutation textbook using metacognitive and mind map strategy for senior high school grade XII. This research adopted ADDIE development model, consisted of Analysis, Design, Development, Implementation, and Evaluation. The textbook was validated by three validators, namely: an education professional, an expert on mutation material, and a biology teacher. The limited trial was conducted on 15 students at SMA Dharma Wanita 4 Taman, Sidoarjo. Data were collected through validation activity, readability test, and questionnaires. Data were analyzed by qualitative descriptive technique. The results indicated that the textbook was stated as valid with a score of 3.82 and practical based on the readability level of 10 (appropriate for senior high school readers) and a very positive response by 96.14%. Based on the data, the mutation textbook using metacognitive and mind map strategy for senior high school grade XII was stated as valid and practical. Keywords: properness, textbook, metacognitive, mind map, mutation.